INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION AND QURAN MEMORISATION IN KUTTAB AL-FIRDAUS LHOKSEUMAWE - Mardhiah, Ainol; Bahri, Saiful (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
Integrating Islamic Religious Education and Qur'anic memorisation at first glance is a common thing to do, because both are included in one family in the science of Islam. However, in real applications, many Islamic educational institutions separate Islamic religious studies and Quranic memorisation so that the two fields of study are separated from each other. Unlike the case with Kuttab Al-Firdaus Lhokseumawe which is able to integrate Islamic religious education and tahfidz Al-Quran in its curriculum. This research includes descriptive-qualitative field research. The findings of this study are, the integration of Islamic religious education materials and tahfidz Al-Quran in Kuttab Al-Firdaus Lhokseumawe is quite well implemented. With several indicators, the way / method of delivery used by tahfidz Al-Quran teachers in integrating Islamic religious education material not only conveys the greatness and power of Allah Subhanahu wata'ala alone, but also the exemplary values of the Prophets and Messengers and Salafusshalihin contained in the Al-Quran. So that the desired goal is enough to achieve results in accordance with the curriculum. Most Tahfidz Al-Quran teachers integrate Islamic religious education material in almost all subject matter studied, as well as assignments and discussions about religion in almost all verses studied in Tahfizd Al-Quran are also well implemented.